Becoming a Mother as a Teenager: Self-Acceptance of Adolescent Girls Who Choose to Get Married - Putri Anisatu Balqis; Sugiariyanti (Developmental and Clinical Psychology, 2024)
Age is one of the essential aspects of everyone's life, including physiological considerations of health and psychological states. At each stage of development, in line with age, a person will face tasks and challenges in life. It is the same as when someone is married, where age also determines the readiness and acceptance of new roles. This study describes the self-acceptance of adolescent girls who do early marriage and motherhood at a young age. The research sources comprised six people, of which two were primary subjects and four were significant others. The criteria for participants used in this study are adolescent girls who married under the age of 19 and have children from the marriage. The method used in this research is qualitative with a phenomenological approach. This research shows that primary informant 1 has good self-acceptance because she can interpret the situation and be responsible for her decisions. Interpret the problem, take responsibility for the decisions, and adjust to her roles as wife and mother. Meanwhile, self-acceptance in primary informant 2 is not good enough because she has yet to view the situation positively and adapt to her role as a wife and mother.